Experimental Progress towards Probing the Ground State of an Electron-Hole Bilayer by Low-Temperature Transport. (29th November 2010) - Das Gupta, K.; Croxall, A. F.; Waldie, J.; Nicoll, C. A.; Beere, H. E.; Farrer, I.; Ritchie, D. A.; Pepper, M.
Abstract : Recently, it has been possible to design independently contacted electron-hole bilayers (EHBLs) with carrier densities< 5 × 10 10  cm 2 in each layer and a separation of 10–20 nm in a GaAs/AlGaAs system. In these EHBLs, the interlayer interaction can be stronger than the intralayer interactions. Theoretical works have indicated the possibility of a very rich phase diagram in EHBLs consisting of excitonic superfluid phases, charge density waves, and Wigner crystals. Experiments have revealed that the Coulomb drag on the hole layer shows strong nonmonotonic deviations from a~T 2 behaviour expected for Fermi-liquids at low temperatures. Simultaneously, an unexpected insulating behaviour in the single-layer resistances (at a highly "metallic" regime withk F l > 500 ) also appears in both layers despite electron mobilities of above ~10 6 cm 2 V − 1 s − 1 and hole mobilities over~10 5 cm 2 V − 1 s − 1 . Experimental data also indicates that the point of equal densities (n = p ) is not special.